Faith, freedom, friendship: cross-cultural affective networks in the correspondence of C F Andrews, E J Thompson, and V H Elwin, India and Europe, 1919 to 1964 - Rogers, DW (2023)
The period from the Amritsar Massacre on 13 April 1919 to the funeral of Jawaharlal Nehru on 28 May 1964 was definitive not only for the establishment of the nation of independent India but also for the global diffusion of the teachings of Mohandas Gandhi and more generally for continuing affective relationships between Indians and Europeans. Charles Freer Andrews, Edward John Thompson, and Verrier Holman Elwin, all three of them (like the author of this thesis) white Anglo-Saxon Protestant males, were led by their religious faith to go to India as Christian missionaries. Their experiences in India caused all three to abandon their affiliations with their churches and to dedicate themselves to the cause of Indian freedom.